STRATEGI PENGEMBANGAN KABUPATEN/KOTA LAYAK ANAK DI KABUPATEN KEBUMEN TAHUN 2019 - Felika Andriani Saputri; Dewi Erowati (Journal of Politic and Government Studies, 2020)
Kebumen District has been given a number of primary rank in the category ofchildren's Worthy Regency (KLA), in 2019 Kabupaten Kebumen increased to the rankof Madya. Due to the increase in the ranking category in the year 2019 in Kebumendistrict as the child Worthy district, the research conducted by this researcher relates tothe strategy used by the District government of Kebumen in Developing KebumenDistrict as a child-worthy district. This research became interesting to be researcheddue to the increase in the ranking category obtained by Kebumen District.The research uses qualitative, descriptive research methods, with datacollection techniques through observation, interviews, and documentation studies. Thesubject in this research is: the Office of Community Empowerment and village andempowerment of women and child Protection, District DPRD Kebumen, children'sForum district, village head of the temple, head of Adikarso village, SMP N 2Kebumen, Puskesmas Karanganyar, and society.The result of this research is describing the findings in the field that is inaccordance with the strategic plan of community empowerment and village andempowerment of women and child protection of Kebumen district which is an increasein capacity Institutional and capacity building of child-friendly services that increasethe establishment of the Village Child Forum, the establishment of child-friendlyschools and the establishment of child friendly puskesmas.From the results of this research, increased establishment of a village childforum, the establishment of child-friendly schools and the establishment of childfriendly puskesmas should continue to be maximally enhanced not only formalitiesmere. In addition, there needs to be an effort to increase the amount of budget that isdoing cooperation with private parties. Then conduct training for the parties related toKLA.Keywords: strategy, development, District worthy children